Genomic landscape and clonal architecture of mouse oral squamous cell carcinomas dictate tumour ecology - Inês Sequeira (Nature Portfolio, 2020)
Modelling oral squamous cell carcinoma (OSCC) is a complex endeavour. Here, the authors provide a comprehensive analysis of an OSCC mouse model and show its mutational signatures mirror human OSCC, providing insights into OSCC clonal dynamics, the microenvironment and evolution.